The Legal Power of Constitutional Court Decisions in the State System: Between Finality and Weak Implementation - Anwar Hidayatulloh, Bagus (PT. Anagata Sembagi Education, 2025)
This study examines the implementation of Constitutional Court (MK) decisions in Indonesia, which, despite being final and binding, often face obstacles. The purpose of this study is to analyze the factors contributing to the weak implementation of MK decisions and to provide recommendations for improving their effectiveness. The study used a qualitative approach with data collection techniques including documentation studies, in-depth interviews, and participant observation. The results indicate that political, institutional, and social factors influence the implementation of MK decisions. Political influence from the executive and legislative branches often hinders the implementation of MK decisions, while weaknesses in the oversight system and a lack of public understanding also contribute to worsening implementation. Therefore, this study recommends institutional reform, increased public awareness of MK decisions, and strengthening the MK's independence from political pressure to improve the effectiveness of MK decision implementation. This research is expected to contribute to strengthening Indonesia's constitutional system and ensuring that MK decisions can be better implemented.